Key competences of outpatient nurses, as perceived by patients attending nurse‐led clinics – An integrative review. Issue 3 (26th November 2020) - Pleh, Denise Nana; Rosted, Elizabeth; Thomsen, Thora Grothe
Abstract: Aim: The aim of this review was to identify key competences of outpatient nurses, as perceived by patients attending nurse‐led clinics. Background: The increased demand for nurses to manage treatment and care in hospital outpatient clinics requires a better understanding of nurses' competences important to outpatients. Design: An integrative review using Whittemore and Knafl's five‐stage model. Methods: Relevant studies were located by systematically searching PubMed, CINAHL and Scopus. A group of three researchers assessed the studies found and the quality of the included studies using the CASP tool. Data were extracted and analysed by thematic analyses. The current study was evaluated using PRISMA checklist. Results: Nine studies met the inclusion criteria. Three key competences emerged: providing access, sharing knowledge and establishing relationships . The key competences were supported by ten sub‐themes that were characterised by nurses' actions and qualities, derived from the included studies. Conclusions: The identified key competences reflected a holistic approach that encompasses knowledge, skills and attitudes, indicating outpatient nurses being able to manage different ways of involving patients, which may lead to the consideration of outpatient consultations as a kind of negotiation, based on a respectful dialogue. Relevance to clinical practice: The findings are usable when optimising the performance and quality of the health workforce, including outpatient nurses, as recommended by WHO (World Health Organization, Global strategy on human resources for health: Workforce 2030, 2016). Furthermore, the identified knowledge emphasises the need for clinical skills training and academic education, specially targeted outpatient nurses, in order to enable the nurses to become experts in specific practice settings.